Hybrid TiO2 photocatalytic ceramic membranes : fabrication, characterization and performance evaluation - Goei, Ronn (2015)
A hierarchically porous hybrid photocalytic membrane was fabricated via layer-by-layer coating of different titanium dioxide (TiO2) sols of varying porous structures onto the macroporous alumina membrane support. The porous structure of the TiO2 layer was fine-tuned by varying the type and amount of different structure directing agents added into the TiO2 sols. Various characterization techniques were employed to elucidate the physico-chemical and morphological characteristics of the resulting TiO2 layers. Different membrane architectures with unique porosity gradient were fabricated. The performance of the membrane was evaluated both in the batch photoreactor and continuous flow Photocatalytic Membrane Reactor (PMR) operated in the dead-end filtration mode. The TiO2 membrane possessed a dual functionality of membrane rejection and photocatalytic activity. The incorporation of Ag nanoparticles into the TiO2 matrix enhanced the photocatalytic activity of TiO2 and added an additional anti-bacterial functionality. Various experiments were conducted to discern different anti-bacterial mechanisms of the Ag-decorated TiO2 membrane. The hierarchically porous hybrid photocatalytic membrane showed a great potential for use in water and wastewater treatment owing to its fouling-control capability, high flux performances, good photocatalytic activity, good anti-bacterial activity and reusability.